Overview of the Mother's Knowledge Level about Handling Diarrhea in Toddlers in Banjar Kepaon Islamic Village - Putri, Ni Kadek Gina Ananda; Andriana, Kiki Rizki Fista; Resiyanthi, Ni Komang Ayu; Mirayanti, Ni Ketut Ayu; Lisnawati, Ketut (Basic and Applied Nursing Research Journal, 2025)
Introduction: Diarrhea in toddlers is a significant health problem in Indonesia, with severe impacts such as dehydration, malnutrition, and death. Environmental, socio-economic factors and limited maternal knowledge about handling diarrhea influence the high incidence rate. Objective: This study aims to describe mothers' level of knowledge about handling diarrhea in toddlers in Banjar Kampung Islam Kepaon. Methods: The research was quantitative descriptive with a purposive sampling technique and involved 115 samples. Data was collected using questionnaires that have been tested for validity and reliability. Results: The results showed that the majority of respondents had a sufficient level of knowledge about handling diarrhea in toddlers, namely 64 respondents (55.7%), of which 57 respondents (49.6%) were 26-35 years old who worked as housewives as many as 64 respondents (55.7%), with the last education of high school/vocational school as many as 62 respondents (53.9%) and obtained information sources through health workers as many as 78 respondents (67.8%). The majority of mothers' knowledge levels were the lowest, related to the question of giving zinc according to age, dehydration condition, and time of administration, which was 37 respondents (32.17%), and the highest was related to the question of bringing toddlers to health services if diarrhea does not improve in 3 days as many as 112 respondents (97.39%). The level of maternal knowledge is quite influenced by exposure to information through health worker education programs. Conclusion: These results show the need for more targeted education-based interventions, especially zinc administration and signs of dehydration, to improve the mother's ability to manage diarrhea optimally.